SUBSURFACE EVOLUTION OF 2006 POSITIVE INDIAN OCEAN DIPOLE - JOHAN (NIM: 22413011); Tim Pembimbing: Ivonne. M. Radjawane, Ph.D.; Dr. Iskhaq Iskandar M.Sc., SEPTI
This Study to know Subsurface Evolution of 2006 positive Indian Ocean Dipole. The data used are SST (Sea Surface Temperature), surface wind, SSH (Sea Surface Height), Zonal current, Zonal current for each dept and temperatur were obtained from Simple Ocean Data Assimilation (SODA), These data were analyzed using a lowpass filter with a cut-off period of 13-monthly to see the phenomenon of IOD and the cut-off period for the 3-month to see the phenomenon of the equatorial waves. The results showed that the evolution of positive IOD 2006 in subsurface occurred longer than the evolution of the surface. Evolution of positive IOD 2006 in subsurface preceding one month earlier and two months longer to ends than the evolution of IOD on the surface. The duration of the evolution of positive IOD 2006 in subsurface is affected by the zonal currents moving eastward during evolution took place.